The Association Between Suicidal Ideation, Explicit Religion and Implicit Religion: An Empirical Enquiry Among 13 to 15 Year-old Adolescents - Francis, Leslie J. (Implicit religion, 2013)
In his analysis of the construct "implicit religion" Edward Bailey speaks of those individuals "who believe in Christianity" but who do not display the behaviours of explicit religion, such as church attendance. A recent research tradition has tried to operationalize this understanding of implicit religion by studying those who believe that they can be a Christian without going to church. A longer established research tradition has demonstrated the association between explicit religiosity and a lower level of suicidal ideation. The aim of the present study is to test the hypothesis that implicit religiosity (in the sense of believing that you can be a Christian without going to church) is also associated with a lower level of suicidal ideation. Data provided by a sample of 25,726 13- to 15- year-old adolescents fail to support this hypothesis.